Clinical outcomes and characteristics of critically ill patients with influenza- and COVID-19-induced ARDS: A retrospective, matched cohort study - Volkov, Lev; Delpuech, Marion; Conrad, Marie; Courte, Guilhem; Cravoisy, Aurélie; Nace, Lionel; Baumann, Cedric; Gibot, Sébastien (Frontiers in Medicine, 2023)
Introduction Seasonal epidemic influenza and SARS-CoV-2 are the most frequent viruses causing acute respiratory distress syndrome (ARDS). To what extent these two etiologies differ in ICU patients remains uncertain. We, therefore, aimed at comparing the severity and outcomes of influenza and SARS-CoV-2-induced ARDS in mechanically ventilated patients. Methods This retrospective, analytic, single-center study was conducted in the medical ICU of Nancy University Hospital in France. Adult patients hospitalized with confirmed influenza (from 2009 to 2019) or SARS-CoV-2-induced ARDS (between March 2020 and May 2021) and those under mechanical ventilation were included. Each patient with influenza was matched with two patients with COVID-19, with the same severity of ARDS. The primary endpoint was death in ICU on day 28. The secondary endpoints were the duration of vasopressors, the use of renal replacement therapy, the duration of mechanical ventilation, and the ICU length of stay. Results A total of 42 patients with influenza were matched with 84 patients with COVID-19. They had similar sex distribution, age, Charlson comorbidity index, and ARDS severity. On day 28, 11 (26.2%) patients in the influenza group and nine (10.7%) patients in the COVID-19 group had died (p = 0.0084, HR = 3.31, CI 95% [1.36–8.06]). In the univariate Cox model, being infected with SARS-CoV-2, SOFA and SAPS II scores, initial arterial pH, PaCO2, PaO2/FiO2, serum lactate level, platelet count, and use of renal replacement therapy were significantly associated with mortality. In the multivariate Cox model, the SOFA score at admission (p < 0.01, HR = 1.284, CI 95% [1.081; 1.525]) and the initial pH (p < 0.01, HR = 0.618, CI 95% [0.461; 0.828]) were the only predictors of mortality. The type of virus had no influence on mortality, though patients with COVID-19 underwent longer mechanical ventilation and received more neuromuscular blockers and prone positioning. Conclusion In mechanically ventilated patients with ARDS, 28-day mortality was higher among patients with influenza as compared to patients with COVID-19 because of a higher initial extra-pulmonary severity. However, the type of virus was not, by itself, correlated with mortality.